Human salivary carbonic anhydrase isoenzyme VI:physiology and association with the experience of dental caries - Kivelä, J. (Jyrki) (University of Oulu, 1999)
Abstract The carbonic anhydrases (CAs) participate in the maintenance of pH homeostasis in various tissues of the human body by catalyzing the reversible reaction CO2 + H2O ⇔ HCO3- + H+. Carbonic anhydrase isoenzyme VI (CA VI) is secreted into the human saliva by the serous acinar cells of the parotid and submandibular glands. The present work was undertaken in order to gain an understanding of the physiological role of CA VI in the oral cavity.